PERKEMBANGAN TINGKAT KEPUASAN PASIEN ANTENATAL CARE (ANC) TERHADAP PERLAKUAN YANG DI BERIKAN DI PUSKESMAS CIMANUK TAHUN 2023 - Aminah (Universitas La Tansa Mashiro, 2025)
The purpose of this study is to obtain information on the development of patient satisfaction ANC to the treatment of pre-test and post-test. This research method was quasi experimental design using time series desigen. The treatment is given by way of presentation of the findings to the head of the health center and all the staff, to be held next repair. Sampling using accidental sampling of 30 people and data collection using questionnaires. The result showed that after treatment there was a increase in satisfaction, when the pre-test values obtained satisfied by 82.71% after treatment increased by 96.51%. In the Cartesian diagram elements is a priority in the pre test is no (9) and (11) and the post test No. (5), (14) and (19). P value between expectation and reality on the pre-test and post test is 0,000 and this means that there is increased after treatment. This increase in satisfaction can be caused by many things, not just the treatment that is given to researchers, but the outside is also very influential variable.